Investigation of the internal behavior in segmented PEMFCs of different flow fields during cold start process. (15th March 2017) - Lin, R.; Ren, Y.S.; Lin, X.W.; Jiang, Z.H.; Yang, Z.; Chang, Y.T.
Abstract: In this study, we have researched the internal behavior in segmented proton exchange membrane fuel cells (PEMFCs) with three different flow fields during cold start process. The change of internal current density and temperature in fuel cells with different flow fields could be obviously shown by the printed circuit board (PCB) technology, and the study shows that the flow field is significant for enhancing the cold start ability and durability. Single serpentine flow field has the best cold start performance, while triple channel serpentine flow field has the best uniformity. It is found that without a robust temperature rising tendency, the cell temperature reaching 0 °C does not definitely mean a successful cold start because the cell temperature might drop down 0 °C again. Polarization curves show that there is almost no performance degradation after successful cold start, but the cell degrades quickly after the failed cold start at −7 °C and −10 °C. Based on these characteristics, we optimized the rapid cold start strategy by using electric heating and make it possible to start up the PEMFC at temperatures down to −20 °C within about 11 min. Highlights: Segmented fuel cell were used to record the internal current density and temperature distributions during the cold start. The effects of flow fields on the PEMFC cold start capacity were evaluated. The effect of cold start on the performance of fuel cell was evaluated. An optimized strategy was adopted to improve the cold start capacity.